PARADIGMA SIMBIOTIK AGAMA DAN NEGARA (STUDI PEMIKIRAN AHMAD SYAFI’I MAARIF) - Muhammad Wahdini (JOURNAL OF ISLAMIC AND LAW STUDIES, 2020)
AbstrakPenelitian ini akan membahas peran epistemologi dalam membangun hukum Islam. Metode yang digunakan melalui kajian pustaka dari beberapa literatur pada studi filsafat hukum Islam. Studi ini menemukan bahwa metode istinbath dengan pendekatan maqashid al-Shari dapat menggabungkan dan memecahkan beberapa masalah hukum yang terjadi dalam konsep perdebatan. Metode ini dianggap efektif dalam mengembangkan konsep hukum Islam sesuai dengan perkembangan zaman dan zaman.Kata kunci: epistemologi; hukum; ijtihadAbstractDiscourse on religious and state relations is increasingly developing among Muslim intellectuals. Likewise the idea of returning Islamic law as a basic principle of statehood in Indonesia has begun to be re-discussed. Ahmad Syafi'i Maarif is one of the influential and phenomenal Muslim intellectual figures in Indonesia. The transformation of his thoughts on religion and the state became interesting, from a fundamental concept to a modernist moralist since he went to Chicago and studied with Fazlur Rahman. After the transformation, Syafi'i Maarif had a symbiotic paradigm about the relationship between religion and the state. Islam needs an instrument called the state. The state is needed to support religion. For Ahmad Syafi'i Maarif, the state is an important tool for religion. However, religion (Islam) does not have to or is the basis of the state.Keywords: Symbiotic Paradigm, Ahmad Syafi'i Maarif, Religion, Country